14-O-[(4, 6-Diamino-pyrimidine-2-yl) thioacetyl] mutilin inhibits α-hemolysin and protects Raw264.7 cells from injury induced by methicillin-resistant S. aureus. (December 2021) - Fu, Yunxing; Yang, Zhen; Zhang, Hongjuan; Liu, Yu; Hao, Baocheng; Shang, Ruofeng
Abstract: A new pleuromutilin derivative, 14- O -[(4, 6-Diaminopyrimidine-2-yl) thioacetyl] mutilin (DPTM), has been synthesized and proven to be a potent agent against Gram-positive pathogens, especially for Staphylococcus aureus ( S. aureus ). However, its pharmacological activities against α-hemolysin (Hla), a major virulence factor produced by S. aureus, and inflammations related to S. aureus are still unknown. In the present study, we investigated the DPTM inhibition activities against methicillin-resistant S. aureus (MRSA) Hla and protective efficacy of Raw264.7 cells from injury induced by MRSA. The results showed that DPTM with sub-inhibitory concentrations significantly inhibited Hla on the hemolysis of rabbit erythrocytes and down-regulated the gene expressions of Hla and agrA with a dose-dependent fashion. In Raw264.7 cells infected with MRSA, DPTM efficiently attenuated the productions of lactate dehydrogenase (LDH), nitric oxide (NO) and pro-inflammatory cytokines, as well as the express levels of nuclear factor-kappaB (NF-κB), nitric oxide synthase (iNOS) and cyclooxygenase-2 (COX-2). Furthermore, DPTM inhibited the translocation of p-65 to nucleus in RAW264.7 cells infected by MRSA. Graphical abstract: Image 1 Highlights: · DPTM significantly inhibited MRSA Hla on the hemolysis of rabbit erythrocytes. · DPTM efficiently attenuated the productions of LDH, NO and pro-inflammatory factors. · DPTM inhibited the expression levels of P-p65, iNOS and COX-2 in Raw264.7 cells. · DPTM inhibited the translocation of p-65 to nucleus.